The Citizens Readiness for E-Government on The Jogja Smart Service (JSS) Application in Yogyakarta City: Kesiapan Masyarakat terhadap E-Government pada Aplikasi Jogja Smart Service (JSS) di Kota Yogyakarta - Yuliantini, Lisa Sophia; Pribadi, Ulung (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2024)
This study aims to analyze the citizens readiness for e-Government on the Jogja smart service (JSS) application in the city of  Yogyakarta. with indicators from Citizens’ readiness for E-Government (CREG), namely ICT Infrastructure, ICT Use, Human Capital, ICT Regulation, and Trust. The research method is quantitative, with questionnaire primary data totaling 100 respondents, and using Smart PLS software version 0.3. in conducting data analysis. The results show that ICT Infrastructure and ICT Use have a significant influence on the citizens' readiness for e-Government in the Jogja Smart Service (JSS) application. Whereas Human Capital, ICT Regulation, and Trust have no significant influence on the citizens' readiness for e-Government in the Jogja Smart Service (JSS) application. The limitation of this study is the number of respondents and the limited number of respondent variables are expected to be used as recommendations for further research.